"Bukan Sekadar Paham": A Quasi-Experimental Study on High School Students in Surabaya - Finsensius Yuli Purnama; Merlina Maria Barbara Apul (Ultimacomm: Jurnal Ilmu Komunikasi, 2023)
This study is a quasi-experimental evaluative research on applying the tagline "Bukan Sekadar Paham", which is the motto of the digital literacy program of Masyarakat Anti Fitnah Indonesia. The main concerns behind this research are: the absence of a quantitative analysis that conducts an empirical investigation of applying the "Bukan Sekadar Paham" discourse in various programs run. Specifically, this article discusses students’ responses in 4 high schools in Surabaya who participated in a digital literacy program entitled Fikom Mengajar. This digital literacy program was held in collaboration between MAFINDO, the MAFINDO Commissariat of Widya Mandala Catholic University Surabaya (UKWMS), and the Student Executive Board, Faculty of Communication Sciences UKWMS. The research was conducted using the theoretical framework of attitude change using the ABC three-dimensional indicators that measure affect, behavior, and cognition. The method used was a survey method, with an electronic questionnaire data collection method on a google form. The results of this study show an increase in the ability to fact-check images, news texts, and posts on social media among high school students in Surabaya. Thus, quantitatively, applying the motto "Bukan Sekadar Paham" is concluded to have been successfully used in the Fikom Mengajar program.